2021
DOI: 10.33448/rsd-v10i13.20814
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulamento de bactérias probióticas: uma breve revisão

Abstract: No cenário econômico global, os probióticos têm sido responsáveis por uma expressiva movimentação financeira, e com crescimento progressivo esperado para os próximos anos. Busca-se cada vez mais otimizar a produção de culturas microbianas desidratadas, o que torna necessário o conhecimento sobre as técnicas disponíveis e já estudadas. O microencapsulamento se destaca por viabilizar a desidratação de microrganismos, de forma a proteger as células dos efeitos negativos da secagem. O objetivo deste artigo foi com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Indeed, the ability of bacteria to survive under gastric digestion conditions is considered a key criterion for probiotic selection (Vieco-Saiz et al, 2022). To overcome this potential drawback strategies of delivery, such as encapsulation, could help the passage through the GIT by protecting bacteria from acidic stress and delivering directly in the intestine where they can act as probiotics and provide health bene ts to the host (Silva et al, 2018;Vianna et al, 2021). A recent study showed that the HigBA TA system of W. cibaria 018 responded to bile salt stress, but not to acid stress, which might offer novel perspectives to understand the tolerance mechanism of probiotics to the GIT environment (Cai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the ability of bacteria to survive under gastric digestion conditions is considered a key criterion for probiotic selection (Vieco-Saiz et al, 2022). To overcome this potential drawback strategies of delivery, such as encapsulation, could help the passage through the GIT by protecting bacteria from acidic stress and delivering directly in the intestine where they can act as probiotics and provide health bene ts to the host (Silva et al, 2018;Vianna et al, 2021). A recent study showed that the HigBA TA system of W. cibaria 018 responded to bile salt stress, but not to acid stress, which might offer novel perspectives to understand the tolerance mechanism of probiotics to the GIT environment (Cai et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of bacteria to survive under gastric digestion conditions is considered a key criterion for probiotic selection [39]. To overcome this drawback, strategies of delivery like encapsulation that could help the passage through the gastrointestinal tract by protecting bacteria from acidic stress and rendering their delivery process directly in the intestine where they can act as probiotics and provide health incentives to the host [40,41]. Recent study showed that the HigBA TA system of W. cibaria 018 responded to the bile salt stress, but not to acid stress, which might offer novel perspectives to understand the tolerant mechanism of probiotics to GIT environment [42].…”
Section: Survival W Cibaria Strains In the Simulated Gastro-intestina...mentioning
confidence: 99%